Mapping elasmobranch occurrences and overlap with human activities using local knowledge and non-invasive sampling to identify areas of potential conflict - Batista, Marisa I.; Abril, Catarina; Veríssimo, Ana; Vasconcelos, Rita P.; Pais, Miguel P.; Henriques, Sofia (Frontiers in Marine Science, 2024)
Over one-third of all elasmobranch species are at risk of extinction worldwide. This study aims to contribute to their conservation worldwide through a case study that combines georeferenced data on species presence and abundance with spatial distribution of human activities, through a Spatial Conflict Risk Index (SCRI). The SCRI pinpoints possible risk areas obtained from the spatial overlap of elasmobranch species abundance and distribution with impacting human activities. Data on species presence and abundance around a Marine Protected Area, the Berlengas Natural Reserve (Portugal) were obtained through four non-invasive methods: Baited Remote Underwater Videos (BRUV), Local Ecological Knowledge (LEK), scientific observers onboard longline commercial fishing vessels and citizen science and social media reports. Human activities were mapped based on LEK. Qualitative abundance and distribution data was obtained for 22 species. SCRI highlighted some high-risk areas due to overlap of areas of frequent occurrence of elasmobranchs with potential high impact activities (e.g. longline fishery). This study highlighted the potential of multi-method approaches to estimate the distribution of rare, highly mobile species in data-limited contexts, and assess their exposure to human activities. The SCRI is a useful tool to support the implementation of effective conservation regulations.